2018
DOI: 10.1021/acsinfecdis.8b00238
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of Two Classes of Selective Inhibitors of the Suppressor of the TCR Signaling Family of Proteins

Abstract: T cells play critical roles in the recognition and elimination of foreign pathogens in the host immune system. The T cell receptor (TCR) is responsible for activating T cells and discriminating between foreign antigens and inappropriate expression of endogenous proteins. Control of T cell signaling occurs through both positive and negative regulation. Two members of the suppressor of TCR signaling (Sts) family of proteins, Sts‐1 and Sts‐2, have been shown to be functionally redundant negative regulator of sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…Intuitively, a higher Z ′ factor (a larger difference between the signals obtained for positive and negative controls and/or smaller standard deviations in their signals) is expected to result in a higher hit rate, although this is also dependent on the statistical cutoff used to determine a hit . In order to confirm whether this expected correlation existed, the confirmed % hit rate for campaigns identified in Table , ,,,,, Table , ,,,,, ,,,,,,, ,,, and several additional papers was plotted as a function of Z ′ factor (Figure ).…”
Section: Other Factors Influencing Hit Identification In Screening Ca...mentioning
confidence: 98%
See 1 more Smart Citation
“…Intuitively, a higher Z ′ factor (a larger difference between the signals obtained for positive and negative controls and/or smaller standard deviations in their signals) is expected to result in a higher hit rate, although this is also dependent on the statistical cutoff used to determine a hit . In order to confirm whether this expected correlation existed, the confirmed % hit rate for campaigns identified in Table , ,,,,, Table , ,,,,, ,,,,,,, ,,, and several additional papers was plotted as a function of Z ′ factor (Figure ).…”
Section: Other Factors Influencing Hit Identification In Screening Ca...mentioning
confidence: 98%
“…In order to investigate this, data were assembled from studies reported in Table , ,,,,, Table , ,,,,, ,,,,,,, ,,,, and several additional papers as noted above. Confirmed % hit rates were plotted as a function of library size (Figure ).…”
Section: Other Factors Influencing Hit Identification In Screening Ca...mentioning
confidence: 99%
“…Several TULA-2 inhibitors and even their classes have been identified, but none of them are ready for the immediate therapeutic use, due to insufficient potency and/or specificity [34,101,102], thus requiring additional studies in this direction. The possibility of using modulation of TULA-2 expression to affect pathological processes has been shown in a mouse model of heparin-induced thrombocytopenia (HIT); anti-miR-148a increases the level of TULA-2 and protects mice from HIT [61].…”
Section: Targeting Tula-family Proteins As a Possible Therapeutic Toolmentioning
confidence: 99%
“…Despite this opportunity, little progress has been made toward the development of Sts inactivators. Prior studies have yielded nonspecific PTP inhibitors, low activity compounds, and nondrug-like hits. , While these demonstrate the druggability of the protein, they do not provide a clear direction for further development nor a foundation upon which to build a lead series. To identify novel inhibitors of the HP activity of Sts-1 (Sts-1 HP ), we recently conducted a 590,000 compound high-throughput screen at The Molecular Screening Center at UF Scripps .…”
Section: Introductionmentioning
confidence: 99%